Health Security Staff And Their Role In Protecting Medical Teams During Mass Casualty Events A Systematic Inquiry (The Review of Diabetic Studies, 2024)
Background: Mass casualty events (MCEs) due to natural disasters, pandemics, industrial incidents, and mass violence, challenge and strain our healthcare systems. In the context of these types of environments, medical teams rapidly triage and intervene to save lives and allocate resources - often in uncontrolled and unsafe scenarios. Although clinical preparedness has received substantial attention, the safety of healthcare workers is an important but largely neglected factor of the emergency response.   Study Objectives: The primary aim of this systematic review is to systematically and critically review and synthesize the current evidence regarding the roles, responsibilities, and effectiveness of health security staff in protecting medical teams during mass casualty events through a lens that is specific to the healthcare system within Saudi Arabia. Materials and Methods: This is a narrative based review study and uses exploratory research design where the data is gathered from various sources on the basis of pre decieded criteria of inclusion and exclusion. PRISMA is used to segregate and screen the collected studies. The results are presented in theoretical and chronological manner to give the clear picture of point in question.Results: The consequences suggest health security personnel are a valuable contributor to operational safety, triage coordination, and psychological protection - operationalizing an interface of clinical preparedness however there seemingly still remains confusion and ambiguity about training, preparedness and integration health security personnel as a distinct front-line responder in institutions.